Amazonia: Mining, taxation, and regional development; Amazônia: mineraç\~ao, tributaç\~ao e desenvolvimento regional - Maurílio de Abreu Monteiro (Novos Cadernos NAEA, 2004)
This paper presents arguments that are the foundation for taxation, charging of royalties, and establishment of fiscal benefits, analyzing the possibilities of using compensations like these to enhance linkages between mining and dynamics of socially rooted development. The paper concludes that there are no public policies in Amazonia for granting fiscal benefits that induce mining companies to adopt behavior that contributes to regional development. It is also observed that royalty rates set in Brazil are relatively low, which is due more to unequal appropriation of political power than to any microeconomic restriction. – – Neste artigo, apresentam-se algumas lógicas que fundamentam a tributaç\~ao, a cobrança de royalties e o estabelecimento de favores fiscais, analisando-se as possibilidades de usar essas compensaç\~oes para favorecer a articulaç\~ao da mineraç\~ao com dinâmicas de enraizamento social do desenvolvimento. Conclui-se que na Amazônia n\~ao há políticas públicas de concess\~ao de favores fiscais que induzam as empresas mineradoras a adotar comportamentos que contribuam para o desenvolvimento regional. Constata-se também que as alíquotas de royalties fixadas no Brasil s\~ao relativamente baixas, o que se deve mais a uma apropriaç\~ao desigual do poder político do que a uma restriç\~ao microeconômica.
Keywords: H32; H73; K34; L72; 330; Amazon; Taxation; Royalties; Mining; Regional development